IMPLEMENTATION OF PRINCIPAL COMPETENCIES IN EFFORTS TO BUILD STUDENT CHARACTER AT SMP KARTIKA XII-1 MERTOYUDAN - Budi Warsana; Nurodin Usman (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
Presidential Regulation (Perpres) Number 87 of 2017 concerning Strengthening Character Education comes with the consideration that in order to create a cultured nation through strengthening religious values, honesty, tolerance, discipline, hard work, creative, independent, democratic, curiosity, enthusiasm nationality, love for the homeland, respect for achievement, communicative, love peace, love to read, care for the environment, care for social, and be responsible, the government sees the need for strengthening character education. So based on these considerations, on September 6 2017, President Joko Widodo has signed Presidential Regulation (Perpres) Number 87 of 2017 concerning Strengthening Character Education. The most appropriate means to realize Presidential Regulation (Perpres) Number 87 of 2017 concerning Strengthening Character Education is through schools, namely the formation or character education for students in schools.